The changing face and associated drivers of research on welfare of the gestating sow - Maria Costanza Galli (Taylor & Francis Group, 2021)
The housing and management of commercial breeding sows is of crucial importance for their productivity and welfare. The aim of the present study is to evaluate how the scientific community addressed the subject of pregnant sow welfare, how it has changed over the past 30 years and what were the drivers of this change. A search of the literature in Scopus identified 318 articles, which were screened for inclusion criteria. Over one hundred of these publications (n = 102) were deemed relevant for the systematic review. Globally, the number of papers on sow welfare during pregnancy increased, but in the last 5 years the trend changed both in terms of publishing country, the interventions studied and the welfare outcomes employed. Up to 2014, published papers about gestating sow welfare came from Europe and North America, with housing system as the most studied topic, followed by nutrition and feeding, and behaviour as the most common welfare outcome. In the last five years, publications from Europe and North America decreased, while publications from Oceania, America Latina and Asia started to appear. Papers on the management of sows in groups and to a lesser extent, environmental enrichment, increased in number. In addition, while prior to 2009 behaviour was the most common welfare outcome, a more diverse range of welfare outcomes were employed in papers in the last 10 years. In order to support new legislation and to respond to consumer requests, future studies should focus on improving sow comfort during gestation.Highlights The changing geographical pattern of papers on sow welfare reflects the growing concerns internationally for animal welfare. Future studies should focus on emerging topics, such as the management of sows in groups and environmental enrichment. It’s important to continue the increasing multidisciplinarity of welfare assessment and to focus on new minimally invasive methods.